Grundtvigs bibelhistoriske sange - Høirup, Henning (Grundtvig-studier, 1992)
Grundtvig's bible historical songs.Bibel historical songs about the old and the new pact, collected and published by Jørgen Glenthøj. Forlaget BHS (Borum Byvej, Borum, 8471 Sabro). 1990. 480 sider. 150 kr.Reviewed by Henning Høirup